ATM Germline-Mutated Gastroesophageal Junction Adenocarcinomas: Clinical Descriptors, Molecular Characteristics, and Potential Therapeutic Implications. (25th January 2022) - El Jabbour, Tony; Misyura, Maksym; Cowzer, Darren; Zimmermann, Michal; Rimkunas, Victoria; Marra, Antonio; Derakhshan, Fatemeh; Selenica, Pier; Parilla, Megan; Setton, Jeremy S; Ceyhan-Birsoy, Ozge; Kemel, Yelena; et al.
Abstract: Background: Gastroesophageal junction (GEJ) adenocarcinoma is a rare cancer associated with poor prognosis. The genetic factors conferring predisposition to GEJ adenocarcinoma have yet to be identified. Methods: We analyzed germline testing results from 23 381 cancer patients undergoing tumor-normal sequencing, of which 312 individuals had GEJ adenocarcinoma. Genomic profiles and clinico-pathologic features were analyzed for the GEJ adenocarcinomas. Silencing of ATM and ATR was performed using validated short-interfering RNA species in GEJ, esophageal, and gastric adenocarcinoma cell lines. All statistical tests were 2-sided. Results: Pathogenic or likely pathogenic ATM variants were identified in 18 of 312 patients (5.8%), and bi-allelic inactivation of ATM through loss of heterozygosity of the wild-type allele was detected in all (16 of 16) samples with sufficient tumor content. Germline ATM -mutated GEJ adenocarcinomas largely lacked somatic mutations in TP53, were more likely to harbor MDM2 amplification, and harbored statistically significantly fewer somatic single nucleotide variants (2.0 mutations/Mb vs 7.9 mutations/Mb; P < .001). A statistically significantly higher proportion of germline ATM -mutated than ATM –wild-type GEJ adenocarcinoma patients underwent a curative resection (10 [100%] vs 92 [86.8%], P = .04; Fisher's exact test.), A synthetic lethal interaction between short-interfering RNA silencing of ATM and ATR was observed in the models analyzed. Conclusions: Our results indicate that germline pathogenic variants in ATM drive oncogenesis in GEJ adenocarcinoma and might result in a distinct clinical phenotype. Given the high prevalence of germline ATM -mutated GEJ adenocarcinomas, genetic testing for individuals with GEJ adenocarcinomas may be considered to better inform prognostication, treatment decisions, and future cancer risk.